2011
DOI: 10.2478/10004-1254-62-2011-2051
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal and Bacterial Pollution of the Sava River in Serbia

Abstract: The aim of this study was to establish microbial and heavy metal pollution of the Sava River at three locations close to industry and urban areas (Šabac, Obrenovac, Beograd) in Serbia. Heavy metal analysis included Cu, Zn, Pb, and Cd in the river water and sediment samples. Using the microbiological analysis we tried to establish the effectiveness of total coliforms, faecal coliforms and Escherichia coli in detecting pollution of surface waters. We found that E. coli levels steadily increased downstream from Š… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…The nonsignificant differences between levels of Cd and Pb in some stations indicate that these metals originate from the same source of pollution. The concentrations of heavy metals in this study were higher than those reported by Salati and Moore (2010) in the Khoshk River at Shiraz, Iran and those found in Sava River in Serbia (Vukovic et al, 2011).…”
Section: Discussioncontrasting
confidence: 53%
“…The nonsignificant differences between levels of Cd and Pb in some stations indicate that these metals originate from the same source of pollution. The concentrations of heavy metals in this study were higher than those reported by Salati and Moore (2010) in the Khoshk River at Shiraz, Iran and those found in Sava River in Serbia (Vukovic et al, 2011).…”
Section: Discussioncontrasting
confidence: 53%
“…[10][11][12] In a previous paper, 13 the results of the distribution and accumulation of heavy metals in the water and sediments of the Sava River displayed seasonal fluctuations, which were attributed mainly to natural processes. The sediment studies were performed mainly because sediments are receptors in water bodies.…”
Section: Introductionmentioning
confidence: 97%
“…Traces of manganese (Mn), iron (Fe), cobalt (Co), bromine (Br), copper (Cu), zinc (Zn), lead (Pb), cadmium (Cd), chromium (Cr), nickel (Ni), and arsenic (As) have been identified in various freshwater bodies throughout the world [ 1 , 9 31 ]. In Canada and the states of Washington and Oregon of the US, the Columbia River, the largest river in the Pacific Northwest region of North America, has been contaminated with heavy metals Cu, Cd, and Zn from metallurgic industries, discharge from municipalities, and mines [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar urban contamination with metals has been reported in the Marcal River of Hungary, rivers of Southeast Asia, west Finland, southeast Brazil, Serbia and central Nigeria, as well as in tributaries of the Nile River in Egypt. The metals most commonly found in these rivers have been Cr, Zn, Cd and Cu [ 9 17 ]. Heavy metals in water pose a worrisome health threat because they tend to be taken up by fish [ 10 , 29 , 32 38 ] and other animals that are used as food sources for humans, such as mollusks and crustaceans [ 19 , 39 46 ].…”
Section: Introductionmentioning
confidence: 99%